Analisis Laporan Keuangan Masjid Da’wah Palembang Berdasarkan PSAK No. 45 Tentang Pelaporan Keuangan Organisasi Nirlaba - Sri Sutandi; Hilwa Anggraini; Masnoni; Zein Ghozali; Lia Sari (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
The purpose of this study is to present the financial statements of the Palembang Da'wah Mosque Foundation based on the Statement of Financial Accounting Standards (PSAK) No. 45 revisions in 2011. The Palembang Da'wah Mosque Foundation in preparing financial reports has not used the guidelines that apply to public sector organizations. One of the ways so that the financial statements of the Palembang Da'wah Mosque Foundation can be easily understood, relevant, and have high comparability, then the Palembang Da'wah Foundation must prepare financial reports based on PSAK No. 45 revised in 2011. The data used aresecondary data. in the form of organizational structure, proof of transactions, and financial reports owned by the mosque. by conducting interviews and documentation. The data analysis technique used descriptive analysis based on the steps of preparing financial statements. The results showed that the characteristics of the information obtained were recording income, expenses, and ending cash balances. Revenues and expenses are only recorded or attached in a standard format and assets are recorded as office inventory. Overall, the implementation of the Financial Statements of Non-Profit Organizations at the Palembang Da'wah Mosque Foundation is not in accordance with the accounting standard regulations of PSAK No. 45 in 2011.